Analisis terhadap Tanggung Jawab Direksi PT Humpus Intermoda Transportasi dalam Tindakan Ultra Vires: Studi Kasus Putusan No. 439/Pdt.G/2011/PN.JKT.SEL - Muhammad Furqon Thoyzar. RH (Mahkamah : Jurnal Riset Ilmu Hukum, 2026)
This study examines the legal accountability of the Board of Directors of PT. Humpuss Intermoda Transportasi in relation to ultra vires conduct, with particular reference to Court Ruling No. 439/Pdt.G/2011/PN.JKT.SEL. Employing a normative-doctrinal legal methodology supported by statutory and comparative analyses, this research investigates the standard of director liability within Indonesian company law and contrasts it with the English ultra vires framework. Indonesia's Limited Liability Company Act (Law No. 40 of 2007) establishes that directors bear full accountability for corporate actions performed within the boundaries set by the Articles of Association and prevailing regulations; any action exceeding such boundaries constitutes an ultra vires act that is void ab initio and non-binding upon the company. Research findings reveal that the directors of PT. Humpuss Intermoda Transportasi overstepped their authority when they issued the Linsen Corporate Guarantee and the Nelson Corporate Guarantee without the mandatory written consent of the Board of Commissioners, thereby contravening Article 13(1) of the Company's Articles of Association and Articles 92(1) and 97(2) of Law No. 40 of 2007. The South Jakarta District Court consequently imposed joint and several personal liability on the said directors. A comparative review discloses that Indonesia maintains a more rigid application of the ultra vires doctrine relative to England, whose Companies Act 2006 introduced a good-faith-based flexibility that effectively confines ultra vires liability to situations where directors act dishonestly and cause demonstrable corporate harm. Notwithstanding this divergence, the directors' actions in the present case would equally qualify as ultra vires under English law given the verified prejudice inflicted on the company.